Formalism and Realism in Ruins (Mapping the Logics of Collapse) - P. Shlag (Теоретическая и прикладная юриспруденция)
After laying out a conventional account of the formalism vs. realism debates, this Article argues that formalism and realism are at once impossible and entrenched. To say they are impossible is to say that they are not as represented — that they cannot deliver their promised goods. To say that they are entrenched is to say that these forms of thought are sedimented as thought and practice throughout law’s empire. We live thus amidst the ruins of formalism and realism. The disputes between these two great determinations of American law continue today, but usually in more localized or circumscribed forms. We see versions of the disputes, for instance, in the stylized disagreements over the desired form of judicial doctrines (rules vs. standards); or the best rendition of key political values like equality (formal vs. substantive); or the proper mode of judicial interpretation (textual vs. purposive). Here too, the arguments that comprise the localized variants of the dispute remain inconclusive. The Article concludes by mapping “the logics of collapse” — specifically, some critical moves that undermine the rhetorical and intellectual force of the formalism vs. realism disputes and their localized variants. The aims here are several. First, the ability to deploy the critical moves helps with analysis. The critical moves help show how the arguments are constructed in the first place and how they are rhetorically and intellectually compromised. Second, and relatedly, the critical moves allow us to avoid being taken in by the formalism vs. realism arguments and their localized variants. Third, the aim is to show how our formalist and realist argumentation has already been surpassed by a legal “logic” that undermines the cogency of that argumentation.